Differential Expression of MUC12, MUC16, and MUC20 in Patients with Active and Remission Ulcerative Colitis - Jesús K. Yamamoto-Furusho; Ilse Ascaño-Gutiérrez; Janette Furuzawa-Carballeda; Gabriela Fonseca-Camarillo (Hindawi Limited, 2015)
Background. Patients with UC have shown an important defect in the secretion and maintenance of the mucosal barrier as part of inadequate expression of mucin genes. The aim of the present study was to determine the expression of MUC12, MUC16, and MUC20 in colonic tissue from patients with UC in regard to their clinical outcomes. Methods. We included a total of 40 patients with UC and 30 normal controls. Mucin gene expression was performed by RT-PCR and protein expression was detected by immunohistochemistry. Results. Patients with active UC showed no significant expression of MUC12 gene in mucosa compared to the group of patients with UC in remission and the normal control group. MUC16 gene expression was significantly increased in the UC active and remission groups compared to the normal control group (P=0.03). MUC20 gene expression was found significantly decreased in patients with active UC compared to both remission group (P=0.001) and normal controls (P=0.001). Furthermore, an association was found between MUC20 gene expression and the presence of histological remission in patients with UC (P=0.003, OR = 0.37). Conclusions. An increased gene expression of MUC16 and MUC20 was found in patients with remission UC.